Brine Shrimp Cytotoxic Activity of Morinda elliptica Leaves and Root Crude Extracts - Henry, Yusufu Wakawa; Fasihuddin, Badruddin Ahmad; Zaini, Assim; Umaru, Isaac John (UNIMAS Publisher, 2017)
This survey was conducted to test for in vivo Brine Shrimp Lethality Assay (BSLA) of Morinda elliptica leaves and root extract after successive maceration in four solvents (n-hexane, dichloromethane (DCM) ethyl acetate and methanol) and cytotoxicity was evaluated in terms of LC50 (lethality concentration). 10 nauplii were placed in different concentrations (in three replicates each) of the plant extracts, after 24 hours the surviving brine shrimp larvae were counted and LC50 was assessed. The result of the survey showed a concentration dependent increment in mortality rate of the brine shrimp nauplii and n-hexane and methanol fractions of the leaves and root extracts were more potent against the brine shrimp with LC50 values of 35.483 ppm and 39.259 ppm (µg/ml) respectively, whereas ethyl acetate of both the extracts exhibited lower potent activity with LC50 values 62.250 ppm and 102.250 ppm (µg/ml) in roots and leaves respectively. These findings indicated that bioactive ingredients are present in the plants that could account for its pharmacological effects.